Socio-Demography, Clinical Characters and Therapy Adherence among Thalassemia Syndromes: Comparative Study in Thi-Qar at 2012-2017 - Ali Jerin Hasson Al-Jaberi (Journal of Global Pharma Technology, 2018)
Thalassemia syndrome is the commonest, well-known monogenetic inherited hematologic disorder that caused by a decrease or an absence of globin production. The study aimed to assess the differences in the socio-emographical characters, clinical finding and adherence to the treatment stratigeis between thalassemia major and other types of thalassemia. An analytical, cross sectional-retrospective- hospital based  study,  including the past 5 years; from 2012  till the end of 2017   in thalassemia center-Al-Habboby hospital-Thiqar health directorate-Iraq.    All the registered cases of thalassemia were included in this study   .The study include 103 patient with mean age of (10.47± 4,936), 52.4% were female, thalassemia major was representing the main proportion (68%) of the studied population, while only(32%) were with other types of thalassemia syndromes such as  sickle thalassemia and thalassemia intermedia, Early age of thalassemia major presentation was the main finding in this study, Al-Nasiriya was the main site of inhabitation. Age of presentation, address, occupation, and educational level, Osteal lesion, growth retardation and carrying of some known complication were of significant association with the different types of thalassemia. Second degree relativeness was the main form of consanguinity among the parents thalassemia major, There was no significant statistical association in adherence to the treatment strategies among the transfusion and non-transfusion dependent thalassemia in their compliance to their applicable regimen. Socio-demography and clinical character are differ among different types of thalassemia, Early age of thalassemia major presentation was the main finding in this study,   osteal lesion, growth retardation, cholelithiasis and infection with viral hepatitis had significant difference, while the consanguinity, blood group and  adherence to the treatment had no significant association.Keywords: Thalassemia , Socio-demography , Thi-Qar.